Piko Hydro Scale 12 Volt For Lighting Requirements in Farmed - Alansyah Putra; Rosdiana Rosdiana; Muhammad Muhammad; Muzamir Isa (Indonesian Scientific Journal, 2022)
The level of consumption of domestic electrical energy is increasing along with the economic growth of the population in Indonesia, especially in Aceh, Gayo Lues Regency is a lot of potential water energy that has not been utilized to produce electrical energy. The pico hydro power plant is a renewable energy that is environmentally friendly, it is expected to be able to utilize the potential of water flow around farmer's plantations, and to find out how much power capacity is generated in the flow of water in farmer's gardens, and aims to find out how much output power the generator will generate from the potential of water flow to be used as a substitute for the use of fossil fuels, as lighting at night and to recharge farmers' electronic equipment in the fields of Gayo Lues Regency. The methodology used for data collection in this study was to collect data directly from the field by means of measurement and testing of tools, the data obtained from this study was by bidding water with a height of water falling on a test of 0.8 meters, 0.9 meters and 1 meter By calculating and analyzing the water discharge that has the potential to produce electric power with an average water discharge of 8.58 m3/s, the type of turbine used in this study is the Kaplan turbine with head adjustment and more specifically for the turbine and alternator with power 40 watts.